2018
DOI: 10.1111/jnc.14264
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of oxidative phosphorylation confers resistance against bevacizumab in experimental glioma

Abstract: Although bevacizumab initially shows high response rates in gliomas and other tumours, therapy resistance usually develops later. Because anti-angiogenic agents are supposed to induce hypoxia, we asked whether rendering glioma cells independent of oxidative phosphorylation modulates their sensitivity against hypoxia and bevacizumab. LNT-229 glioma cells without functional mitochondria (rho ) and control (rho ) cells were generated. LNT-229 rho -cells displayed reduced expression of oxidative phosphorylation-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Strikingly, patients who showed a mitochondrial signature in their tumour tissue had significantly better overall survival following Bev treatment. These findings are consistent with experimental data demonstrating that glioma cells without functional mitochondria are resistant to Bev [51]. Although this finding needs to be validated in larger cohorts of patients, these pilot data are compatible with the hypothesis that tumours with a mitochondrial signature are susceptible to anti‐angiogenic therapy because they are less capable of adapting their metabolism to conditions of Bev‐induced hypoxia.…”
Section: Discussionsupporting
confidence: 89%
“…Strikingly, patients who showed a mitochondrial signature in their tumour tissue had significantly better overall survival following Bev treatment. These findings are consistent with experimental data demonstrating that glioma cells without functional mitochondria are resistant to Bev [51]. Although this finding needs to be validated in larger cohorts of patients, these pilot data are compatible with the hypothesis that tumours with a mitochondrial signature are susceptible to anti‐angiogenic therapy because they are less capable of adapting their metabolism to conditions of Bev‐induced hypoxia.…”
Section: Discussionsupporting
confidence: 89%
“…Upregulation of HIF-1a can promote neovascularization by promoting tumor cells to produce pro-angiogenic factors such as PDGF-B, FGF-2, VEGF-A, VEGFR1 and angiopoietins [ 252 ]. Hence, highly glycolytic metabolism can be considered as a metabolic feature regarding the resistance to Bevacizumab [ 249 , 253 ]. Furthermore, Xu et al found that CRC cells refractory to bevacizumab treatment not only undergo hyperactive glycolytic phenotype, but also occur persistent impairment of mitochondria [ 254 ].…”
Section: Warburg Effect Promotes Drug Resistance In Crcmentioning
confidence: 99%
“…The development of a more glycolytic phenotype as an escape mechanism has been postulated in bevacizumab treated tumor cells [35]. Our group reported that in an orthotopic mouse xenograft model, glioma with impaired oxidative phosphorylation were resistant to treatment with bevacizumab, and treatment with 2-DG re-established sensitivity to bevacizumab [36]. Therefore, antagonizing glycolysis and neoangiogenesis together could be a promising therapeutic concept.…”
Section: Discussionmentioning
confidence: 99%